The Potential Impacts of The East African Crude Oil Pipeline (EACOP) On Human Rights in Uganda. - Mugabi. K. Ivan. (ssrn.com, 2023)
This paper is primarily centered on interaction between the advancement of the East African Crude Oil Pipeline (herein after the EACOP) on one hand and aspects of human rights on the other hand. This paper shall seek to borrow ideas from land rights, environmental rights and other right based narratives in demonstrating how and why the EACOP project is not only the most exciting socioeconomic but also a project giving room for opposing phenomenological discourses most of which are hinged upon ideas of human rights. This analysis shall therefore adopt a comparative as well as a reflective research design in asserting that in as much as the project is economically viable, lesson must be picked from other developing regions where similar projects have culminated into detrimental consequences upon the communities